Histopathology Of Organ Tissues In Dengue Fever Patients: A Narrative Review - Herman, Hastuti; Sunarto , Sunarto (CV. Publikasi Indonesia, 2025)
Dengue hemorrhagic fever is one of the tropical diseases that is still a global public health problem, this is closely related to the environmental conditions that support the life cycle of the Aedes species mosquito, which is the vector of its spread. Laboratory testing to support diagnosis is generally by examining viral or serological components. The technique is limited to the acute phase, so the role of histopathological aspects that explain changes in tissue structure in organs is significant. The histopathology reports of dengue hemorrhagic fever patients in this literature review will be summarized so that they can be used as a reference source for medical laboratory technology students, strengthening understanding of the tissue pathology of dengue virus infection. A total of ±126 million academic articles, reduced to the 50 papers most relevant to the research question. There are 7 articles that meet the criteria. Post-infectious organ tissue in dengue hemorrhagic fever patients, showing various conditions such as necrosis, edema, hemorrhage, vascular congestion in various organs; infiltration of inflammatory cells; viral replication characterized by the expression of dengue virus antigens in various cells; as well as the expression of chemokines and cytokines.